The Influence of Organizational Culture and Job Stress on Employee Performance Through Job Satisfaction as An Intervening Variable at Center for Expansion of Employment Opportunities Bekasi - Muhamad Apip; Harry Indratjahyo; Muhamad Harri (Journal of Islamic Studies & Social Science, 2024)
This study aims: 1) analyze the effect of organizational culture on employee performance on BPKK Bekasi 2) analy ze the influence of work stress on employee performance on BPKK Bekasi. 3) analyze the influence of organization al culture on job satisfaction on BPKK Bekasi 4) analyze the effect of work stress on job satisfaction on BPKK Bekasi. 5) analyze the effect of job satisfaction on employee performance on BPKK Bekasi. 6) analyze the influence of organizational cult ure on employee performance through job satisfaction on BPKK Bekasi. 7) analyze the effect of work stress on em ployee performance through job satisfaction on BPKK Bekasi. This research used quantitative approach. This resea rch used descriptive method. The population in this study is 50 employees. In this research, the sa mpling technique used is nonprobability sampling with the technique taken that is saturated sampl ing (census), taken a sample of 50 employees at Bekasi employment opportunity expansion Hall a s respondents in this study. The design of analysis and hypothesis test using path analysis (Path Analysis) processed using SPSS. The results of this study: 1) there is a significant influence of organizational culture on employee performance on BPKK Bekasi. 2) there is a significant influence of Job stress on employee performance on BPKK Bekasi.3) there is a significant effect of organizational culture on job satisfaction on BPKK Bekasi. 4) There is a significant influence of job stress on job satisfaction BPKK Bekasi. 5) there is no significant effect of job satisfaction on employee performance on BPKK Bekasi. 6) There is a significant influence of organizational culture on employee performance through job satisfaction on BPKK Bekasi. 7) There is a significant effect of job stress on employee performance through job satisfaction on BPKK Bekasi.